Has US monetary policy followed the Taylor rule? A cointegration analysis 1988-2002 - Anders Møller Christensen; Heino Bohn Nielsen (Danmarks Nationalbank, 2003)
Based on the equilibrium correction structure of a cointegrated vector autoregression it is rejected that US monetary policy 1988-2002 can be described by a traditional Taylor (1993) rule. Instead we find a stable long-term relationship between the Federal funds rate, the unemployment rate, and the long-term interest rate, with deviations from the long-term relation being corrected primarily via changes in Federal funds rate. This is taken as an indication that the FOMC sets interest rates with a view to activity and to expected inflation and other conditions available in financial markets.
Keywords: C32; E52; 330; Taylor rule; Bond rate; Cointegration; Equilibrium Correction; Taylor-Regel; Geldpolitik; Kointegration; USA; Gleichgewicht